Systematic Literature Review: Inkonsistensi Pengaruh Sosialisasi Pajak dan Konsistensi Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak - Syaifudin Syaifudin; Kasih Purwantini; Edy Susanto; Ayu Miranti Kusumaningrum (CV. Denasya Smart Publisher, 2026)
This study compares the effect of tax socialization and tax punishments on taxpayer compliance based on five empirical studies from distinct locations in Indonesia. The analysis shows considerable inconsistencies in the results. Some research demonstrated a beneficial effect on tax compliance of taxpayers with respect to tax socialization, some showed no meaningful effect. With regard to tax sanctions, most of the research revealed a considerable positive effect, although one study argued that sanctions had no effect since internal tax payer awareness was dominant. Additional studies support the idea that the connection between these two variables is not simple. Effectiveness of socialization and penalties is very dependent on contextual factors, such as respondent characteristics, geographic location, and perceptions of fairness. The most important internal factor found to promote voluntary compliance is taxpayer awareness. The comparison ends with the conclusion that there is no universally effective method for all regions. Holistic approach to promote tax compliance in Indonesia includes innovative socializing, firm and fair implementation of penalty, and continual enhancement of taxpayer knowledge